Biofilm formation in Pseudoalteromonas lipolytica is related to IS5-like insertions in the capsular polysaccharide operon. Issue 6 (11th May 2019) - Zeng, Zhenshun; Zhan, Waner; Wang, Weiquan; Wang, Pengxia; Tang, Kaihao; Wang, Xiaoxue
ABSTRACT: Bacterial capsular polysaccharides (CPSs) participate in environmental adaptation in diverse bacteria species. However, the role and regulation of CPS production in marine bacteria have remained largely unexplored. We previously reported that both wrinkled and translucent Pseudoalteromonas lipolytica variants with altered polysaccharide production were generated in pellicle biofilm-associated cells. In this study, we observed that translucent variants were generated at a rate of ∼20% in colony biofilms of P. lipolytica cultured on HSLB agar plates for 12 days. The DNA sequencing results revealed that nearly 90% of these variants had an IS 5 -like element inserted within the coding or promoter regions of nine genes in the cps operon. In contrast, IS 5 insertion into the cps operon was not detected in planktonic cells. Furthermore, we demonstrated that the IS 5 insertion event inactivated CPS production, which leads to a translucent colony morphology. The CPS-deficient variants showed an increased ability to form attached biofilms but exhibited reduced resistance to sublethal concentrations of antibiotics. Moreover, deleting the DNA repair gene recA significantly decreased the frequency of occurrence of CPS-deficient variants during biofilm formation. Thus, IS insertion into the cps operon is an important mechanism for the production of genetic variants during biofilm formation of marine bacteria. Abstract : Translucent variants of Pseudoalteromonas lipolytica generated during biofilm formation had an IS5 insertion element inserted within the coding or promoter regions of nine genes in the cps operon.